Nursing performance in the face of sexuality in the senescence process: an experience report (Research, Society and Development, 2020)
Aging is configured as a set of physiological changes that occur gradually in the lives of all individuals, being linked to several stigmas that can affect the quality of life of the elderly population, especially sexuality in the elderly. Thus, reiterating the fundamentality of this theme, this study aimed to describe a health education action aimed at the elderly in a Health Center in Belém-PA, which discussed the healthy aging process and the aspects that involve the sexuality of the elderly, seeking to promote the empowerment of this public, as well as highlight the importance of sexual health. This study is characterized as descriptive with a qualitative approach, of the experience report type, which talks about the theoretical-practical experience of nursing students. To support the work, the Theory of Problematization was used through the Arco de Maguerez methodology. The main results found showed that several factors may be responsible for the abdication of sexuality in old age, among them the family influence, the fear of social judgments and the shame in debating the theme with the elderly partner. In addition, the role of the nurse was confirmed to enable the effective and healthy coping of the aging process and health promotion. In this way, the importance of the activity carried out was reiterated, since it provided public awareness of the relevance of the theme and emphasized its influence on health, in addition to promoting individual self-care.